Аттрактори динамічних систем з керуванням: топологія цілеспрямованого формування - Спаравало, М.К. (Український математичний журнал, 1995)
The definitions of homogeneous and mosaic attractors of codimension one are given. A topological method for their purposeful formation by using the feedback control laws of controlled dynamical systems is suggested.